117k views
15 votes
G(x) =2x + 4; Find g(-3)

User Ivoszz
by
5.4k points

2 Answers

5 votes

Answer: -2

Explanation:

plug g(x) with -3 so it would be 2(-3) + 4 and then simply and add so 2(-3) equals -6 + 4 is -2

User Pragalathan  M
by
5.5k points
6 votes

Answer:


g(-3)=-2

Explanation:

Substitute g(-3) into the function:


g(-3)=2(-3)+4

Multiply:


g(-3)=-6+4

Add:


g(-3)=-2

User Yusuf Cum
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.